Circumdatin D Exerts Neuroprotective Effects by Attenuating LPS-Induced Pro-Inflammatory Responses and Downregulating Acetylcholinesterase Activity In Vitro and In Vivo - Zhang, Chanjuan; Hu, Likun; Liu, Dong; Huang, Jian; Lin, Wenhan (Frontiers in Pharmacology, 2020)
Alzheimer's disease (AD) is a prevalent neurodegenerative disorder with multifactorial causes, of which systemic inflammation may play a key role to promote neurodegeneration, and acetylcholinesterase (AChE) is a target to induce cholinergic transmission. Inhibitors toward inflammation and AChE improve cholinergic signaling in the central nervous system in the therapy of AD. During the search for neuroprotection agents from marine-derived compounds, seven circumdatin-type alkaloids from a coral-associated fungus Aspergillus ochraceus LZDX-32-15 showed potent inhibition against lipopolysaccharide (LPS)-induced nitric oxide production and activation of NF-κB report gene along with anti-AChE activities. Circumdatin D performed the best among the tested compounds. In vivo experiments using AD-like nematode models demonstrated that circumdatin D effectively delayed paralysis of CL4176 worms upon temperature up-shift via suppression of AChE activity and inflammatory-related gene expression. Moreover, circumdatin D interfered with inflammatory response by inhibiting the secretion of pro-inflammatory cytokines in LPS-induced BV-2 and primary microglia cells. Mode of action investigation revealed that circumdatin D modulated Toll-like receptor 4 (TLR4)-mediated NF-κB, MAPKs and JAK/STAT inflammatory pathways in LPS-stimulated BV-2 cells, and protected primary neurons cells from LPS-induced neurotoxicity. Thus, circumdatin D is considered as a potential agent for neuroprotective effects by the multi-target strategy.